The Influence of Word of Mouth Talkers and Tools on Consumer Buying Decisions in Sate Taichan Shincan Palembang - Indah Tri Satriani; Siti Komariah; Muhammad Wadud (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to determine the effect of Word of Mouth Talkers and Tools on Consumer Buying Decisions at Sate Taichan Shinchan Palembang Restaurant. Data was obtained through the distribution of questionnaires and interviews. The sample in this study was 178 consumers. The results showed that there was a positive influence between the influence of word of mouth talkers on buying decisions. The results obtained from the value of the Multiple Linear Regression Coefficient of 5,600 means that the increase in the value of Word of Mouth Talkers and Tools spread by 1 unit will increase the value of consumer purchases by 5,600. The results of the study obtained the value of the Correlation Coefficient (R) between Word of Mouth Talkers and Word of Mouth Tools on the Buying Decision variable, which has a moderate relationship because it has a correlation value of 0.506 (50.6%). Furthermore, research using the analysis of the Coefficient of Determination (R2) explained by Word Of Mouth Talkers, and Word of Mouth Tools, of 25.6% while the rest of 74.4% can be explained by other factors.